Métodos de avaliação da musculatura do assoalho pélvico feminino - Pereira, Vanessa Santos (2013)
Proper assessment of the pelvic floor muscles is essential for the correct pelvic floor dysfunctions treatment. However, currently there is not a method considered as the gold standard assessment. Therefore, this thesis aimed to evaluate the reliability of different methods to normalize pelvic floor muscles electromyography (EMG) and the determination of the correlation among vaginal palpation, vaginal squeeze pressure, EMG and ultrasonographic variables of female pelvic floor muscles. For the first aim, we evaluated 30 women aged (23,9 ±3,2 years), nulliparous, with no reports of pelvic floor dysfunction. For EMG normalization, signals were acquired during four different tasks were performed with the vaginal probe in situ: pelvic floor maximal voluntary contraction (MVC) and three daily activities with increased intra-abdominal pressure (coughing, Valsalva maneuver and abdominal contraction). The results showed that the normalization of pelvic floor muscles EMG by either peak RMS of pelvic floor MVC or mean and peak RMS of abdominal contraction has excellent reliability. To analyze the correlation between the different methods of pelvic floor evaluation we evaluated 80 women and it was carried out the digital palpation, perineometry, EMG and ultrasound. It was observed that there is a positive strong correlation between digital palpation and vaginal pressure, besides positive moderate correlation between the function and vaginal pressure contraction and RMS normalized by abdominal contraction (0.59 and 0.63, respectively), and between movement of bladder neck in relation of pubic symphysis (0.51 and 0.60, respectively). In conclusion, the results demonstrated that the normalization of pelvic floor muscles EMG by the mean and peak RMS of abdominal contraction and by the peak RMS of pelvic floor MVC should be indicated in studies involving EMG evaluation of pelvic floor muscles in young, nulliparous and free from pelvic floor dysfunction women. In addition, the moderate to weak correlation between the evaluation methods indicates that using more than one method can be positive in the assessment of pelvic floor muscles.